Zirconium phosphate nanosheet reinforced composite hydrogel electrolyte as well as preparation method and application thereof

By using zirconium phosphate nanosheets to enhance composite hydrogel electrolytes in aqueous zinc ion batteries, the problems of battery stability and cycle life are solved, higher mechanical strength, interface stability and zinc ion conductivity are achieved, and the service life of the battery is extended.

CN119812458AActive Publication Date: 2025-04-11LINYI UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510033406.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

Existing aqueous zinc ion batteries have challenges in terms of stability and cycle life, mainly due to the metal ion dissolution in the cathode material and the corrosion of zinc metal, resulting in poor interface stability and low energy density.

Method used

Zirconium phosphate nanosheets are used as enhancers to enhance the mechanical strength and interface stability of the hydrogel electrolyte by forming hydrogen bonds or electrostatic effects with the polymer, and regulate the zinc ion solvation structure through zinc-philic functional groups to inhibit dendrites' growth and by-product production.

Benefits of technology

It significantly improves the tensile strength, puncture strength and zinc ion conductivity of hydrogel electrolytes, extends the cycle life of zinc ion batteries, and shows long cycle stability at room temperature and high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812458A_ABST
    Figure CN119812458A_ABST
Patent Text Reader

Abstract

The invention discloses a zirconium phosphate nanosheet reinforced composite hydrogel electrolyte as well as a preparation method and application thereof, and belongs to the technical field of preparation of semi-solid electrolyte materials. The zirconium phosphate nanosheet reinforced composite hydrogel electrolyte is formed by selecting a zirconium phosphate nanosheet as an inorganic cross-linking agent and doping a proper amount of metal salt with a polymer monomer, the mechanical strength, the ionic conductivity and the interface stability of the composite hydrogel electrolyte are all greatly improved, and the gel electrolyte is suitable for an aqueous zinc ion battery; the corrosion of a zinc negative electrode and the dissolution of a positive electrode material are slowed down, the cycle life of the battery is prolonged, and the market application prospect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semi-solid electrolyte material preparation, and specifically relates to a zirconium phosphate nanosheet reinforced composite hydrogel electrolyte and a preparation method and application thereof. Background Art

[0002] Accelerating the exploration and deployment of renewable energy is of great significance for mitigating catastrophic climate change and promoting sustainable development. However, renewable energy sources such as solar and wind energy are subject to intermittent characteristics due to changes in sunshine, geographical location and seasonality. Therefore, it is necessary to find solutions for storing green energy to achieve its widespread application. Lithium-ion batteries, as a mature electrochemical energy storage device, have significant advantages in energy density and service life. Unfortunately, scarce resources such as Li and Co, safety issues and high manufacturing costs limit the widespread application of lithium-ion batteries in the field of energy storage. In recent years, aqueous batteries have become a hot spot in energy storage research due to their convenient preparation, abundant resources and high safety. Compared with alkali metals, zinc metal has unique appeal as an anode for aqueous batteries. This is attributed to its excellent specific capacity (820 mAh / g, 5851 mAh / cm 3 ), low redox potential (-0.76 V vs SHE), and low manufacturing cost. However, achieving high energy density remains challenging because the cathode and anode materials are not always stable enough in aqueous electrolytes. For example, the metal ions in the cathode material gradually dissolve during the cycle, and zinc metal is susceptible to corrosion and dendrites during repeated cycles. These problems are closely related to the high chemical activity of water, which seriously hinders the commercialization of aqueous zinc-ion batteries.

[0003] Hydrogel electrolytes can replace liquid electrolytes and separators in traditional batteries and guide the migration and diffusion of ions. The polymers in hydrogel electrolytes contain abundant hydrophilic groups, such as -OH, -COOH, -NH2 or -CONH2. These hydrophilic groups can form hydrogen bonds with water molecules. Increasing the number of hydrogen bonds can stabilize the water molecules in the polymer matrix and reduce the oxygen or hydrogen evolution reaction of the hydrogel during application. Due to the low water content in the gel electrolyte, a solid-solid interface is introduced between the electrode and the electrolyte instead of a solid-liquid interface, resulting in poor interface stability. At present, the main polymer materials of common hydrogel electrolytes include polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyacrylamide (PAM), gelatin, alginate, agarose, and chitosan. However, there are still some challenges in the preparation of hydrogel electrolytes using a single polymer, including low ionic conductivity, insufficient mechanical strength, and large thickness.

[0004] In response to the above problems, this patent uses zirconium phosphate nanosheets as a reinforcing agent to increase the mechanical strength, ionic conductivity and interface stability of the gel electrolyte. So far, there has been no report on the use of zirconium phosphate two-dimensional nanosheets as a reinforcing agent to prepare hydrogel electrolytes and apply them to zinc ion batteries. Summary of the invention

[0005] The purpose of the present invention is to provide a zirconium phosphate nanosheet reinforced composite hydrogel electrolyte and a preparation method thereof, select zirconium phosphate two-dimensional nanosheets as an inorganic crosslinking agent to enhance the mechanical strength of the hydrogel electrolyte, prepare a hydrogel electrolyte with a smaller thickness, and at the same time improve the ionic conductivity and interface stability.

[0006] In order to achieve the above technical objectives, the technical solution adopted by the present invention is: A method for preparing a zirconium phosphate nanosheet reinforced composite hydrogel electrolyte, comprising the following steps: (1) α-zirconium hydrogen phosphate, ethanolamine and deionized water are mixed to obtain a mixed solution, which is reacted at room temperature for 24-48 hours, and then unreacted ethanolamine is removed by dialyzing with a dialysis bag, and then the suspension is centrifuged at a certain speed, and the upper layer of the suspension after centrifugation is the zirconium phosphate nanosheet dispersion; (2) mixing the zirconium phosphate nanosheet dispersion, polymer monomer, initiator, cross-linking agent and metal salt in proportion at room temperature to obtain a gel electrolyte precursor solution; (3) Pour the above-mentioned gel electrolyte precursor solution into a glass mold and react at 60°C for 1-5 hours. After the reaction is completed, a zirconium phosphate nanosheet-reinforced composite hydrogel electrolyte is obtained.

[0007] Preferably, in the mixed solution in step (1), the mass fraction of α-zirconium hydrogen phosphate is 1-4%, and the mass fraction of ethanolamine is 2-8%.

[0008] Preferably, the solid content of the zirconium phosphate nanosheet dispersion in step (1) is 0.5-2 wt%.

[0009] Preferably, the centrifugal separation speed in step (1) is 10000 rpm / min and the time is 2 min.

[0010] Preferably, in the gel electrolyte precursor solution, the polymer monomer concentration is 2-6 mol / L, the initiator concentration is 3-9 mmol / L, the crosslinker concentration is 0.5-1.4 mmol / L, and the metal salt concentration is 2-3 mol / L.

[0011] Preferably, the polymer monomer is acrylamide or acrylic acid, the initiator is ammonium persulfate or potassium persulfate, and the crosslinking agent is N,N'-methylenebisacrylamide.

[0012] Preferably, the metal salt is a zinc salt, a mixed salt of a zinc salt and a manganese salt in a molar ratio of 20:1, or a mixed salt of a zinc salt and a lithium salt in a molar ratio of 2:1 or 1:1.

[0013] Preferably, the zinc salt is one or more of zinc sulfate, zinc nitrate, zinc perchlorate, zinc acetate, zinc chloride, zinc trifluoromethanesulfonate, and zinc bis(trifluoromethylsulfonyl)imide; the lithium salt is one or more of lithium sulfate, lithium nitrate, lithium chloride, lithium perchlorate, lithium acetate, lithium trifluoromethanesulfonate, and lithium bis(trifluoromethanesulfonyl)imide; the manganese salt is one or more of manganese sulfate, manganese nitrate, manganese chloride, manganese perchlorate, and manganese acetate.

[0014] A zirconium phosphate nanosheet reinforced composite hydrogel electrolyte is prepared by the above method. The zirconium phosphate nanosheet reinforced composite hydrogel electrolyte prepared by the present invention can be applied to aqueous zinc ion batteries and has good application effects.

[0015] Zirconium hydrogen phosphate is a layered material. The interlayers of zirconium hydrogen phosphate contain abundant P-OH active groups. These groups easily lose protons H in aqueous solution, making the surface of the layer negatively charged. Zirconium hydrogen phosphate is stripped before use to prepare zirconium phosphate two-dimensional nanosheets. First, the surface of zirconium phosphate nanosheets contains a high density of acidic functional groups - PO3 - , can form hydrogen bonds with hydrophilic functional groups, or form electrostatic interactions with positively charged functional groups. These chemical and physical cross-linking structures can jointly enhance the mechanical strength of the hydrogel electrolyte, thereby helping to reduce the thickness of the gel electrolyte. Secondly, the zinc-philic functional groups on the surface of zirconium phosphate nanosheets give it a higher binding energy with zinc atoms or zinc negative electrodes, thereby regulating the zinc ion solvation structure and enhancing the interface stability. Finally, the gel electrolyte is used in zinc-ion batteries to inhibit the dissolution of active substances on the positive electrode side, while inhibiting the growth of dendrites and the generation of by-products on the negative electrode side, thereby extending the cycle life of zinc-ion batteries.

[0016] Compared with the prior art, the present invention has the following advantages: 1) The preparation process of zirconium phosphate nanosheet-enhanced composite hydrogel electrolyte is simple, the raw materials are cheap, the reaction process is safe and environmentally friendly, and it has the potential for large-scale production.

[0017] 2) Zirconium phosphate nanosheets can form hydrogen bonds or electrostatic interactions with polymers to increase the mechanical strength of the hydrogel electrolyte. Compared with single polymer gel electrolytes, the addition of zirconium phosphate nanosheets significantly improves the tensile strength and puncture strength of the gel electrolyte.

[0018] 3) The surface of zirconium phosphate nanosheets is zinc-philic, and the hydrophilic functional groups on the polymer surface can fix water molecules. Under the synergistic effect of the two, the solvation structure of zinc ions can be changed, thereby promoting zinc ion transport. The prepared zirconium phosphate nanosheet-enhanced composite hydrogel electrolyte improves the interface stability and long cycle performance. Compared with traditional aqueous electrolytes and single polymer gel electrolytes, the addition of zirconium phosphate nanosheets can inhibit the growth of zinc dendrites and promote the uniform deposition of zinc ions.

[0019] 4) Compared with traditional aqueous electrolytes and single polymer gel electrolytes, high-performance zinc-ion batteries constructed with zirconium phosphate nanosheets reinforced composite hydrogel electrolytes exhibit longer cycle life at both room and high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Comparison of the tensile strength of polyacrylamide hydrogel electrolyte (PAM) and zirconium phosphate nanosheets reinforced polyacrylamide hydrogel electrolyte (ZrP-PAM); Figure 2 To compare the puncture strength of polyacrylamide hydrogel electrolyte (PAM) and zirconium phosphate nanosheets reinforced polyacrylamide hydrogel electrolyte (ZrP-PAM); Figure 3 Comparison of zinc ion transference number (a) and zinc ion conductivity (b) of liquid electrolyte (LE), polyacrylamide hydrogel electrolyte (PAM) and zirconium phosphate nanosheets reinforced polyacrylamide hydrogel electrolyte (ZrP-PAM); Figure 4 Surface scans of zinc anode before and after cycling, (a) scanning of zinc anode before cycling, (b) scanning of zinc anode after 50 cycles in liquid electrolyte (LE), (c) scanning of zinc anode after 50 cycles in polyacrylamide hydrogel electrolyte (PAM), (d) scanning of zinc anode after 50 cycles in zirconium phosphate nanosheet enhanced polyacrylamide hydrogel electrolyte (ZrP-PAM); Figure 5 Soft-pack battery assembled with zinc foil and lithium manganese oxide (LMO) and its cycling stability, (a) Photographs of zinc foil and lithium manganese oxide electrodes, (b) Zn||LMO soft-pack battery at 50 o C, (c) Cyclic performance of Zn||LMO soft package at 25℃. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.

[0022] Example 1 A zirconium phosphate nanosheet-enhanced hydrogel electrolyte is prepared by the following method: 1) Add 2 g of α-zirconium hydrogen phosphate and 4 mL of ethanolamine to 100 mL of deionized water and stir at room temperature for 48 h; w = 1000) to remove unreacted ethanolamine. The pH of the suspension after dialysis was about 7. The suspension was centrifuged at 10000 rpm / min for 2 min. The upper layer after centrifugation was the zirconium phosphate nanosheet dispersion. The solid content of the zirconium phosphate nanosheet in the dispersion was determined by calculating the mass ratio of the water solvent in the dispersion before and after drying. The solid content of the zirconium phosphate nanosheet was 1wt%, and the thickness of the prepared zirconium phosphate nanosheet was 2-4 nm.

[0023] 2) 4 g acrylamide monomer was dissolved in 10 mL 1 wt % zirconium phosphate nanosheet dispersion and then magnetically stirred at room temperature for 1 h; then 5.75 g ZnSO4·7H2O, 1.24 g Li2SO4·H2O, 0.02 g initiator ammonium persulfate (APS, 99.9% Aladdin) and 0.002 g cross-linker N, N'-methylenebisacrylamide (MBAA, 99.9% Aladdin) were added to the above solution and stirred at room temperature until they were completely dissolved to obtain a mixed solution.

[0024] 3) The mixed solution was poured into a glass mold and polymerized at 60 °C for 4 h to obtain a zirconium phosphate nanosheet-enhanced hydrogel electrolyte. The water content of the obtained gel electrolyte was 57%.

[0025] Example 2 A zirconium phosphate nanosheet-enhanced hydrogel electrolyte is prepared by the following method: 1) Add 1 g of α-zirconium hydrogen phosphate and 2 mL of ethanolamine to 100 mL of deionized water and stir at room temperature for 48 hours; dialyze the mixture in a dialysis bag (Mw = 1000) to remove unreacted ethanolamine. The pH of the suspension after dialysis is about 7. Centrifuge the suspension at 10,000 rpm / min for 2 min. The upper layer after centrifugation is the zirconium phosphate nanosheet dispersion. The solid content of zirconium phosphate in the dispersion is determined by calculating the mass ratio of the water solvent in the dispersion before and after drying. The solid content of the zirconium phosphate nanosheet is 0.5wt%, and the thickness of the prepared zirconium phosphate nanosheet is 2-4 nm.

[0026] 2) 2 g of acrylamide monomer was dissolved in 10 mL of 0.5 wt % zirconium phosphate nanosheet dispersion and then magnetically stirred at room temperature for 1 h. Subsequently, 5.75 g of ZnSO4·7H2O, 0.007 g of initiator ammonium persulfate (APS, 99.9% Aladdin) and 0.008 g of cross-linker N, N'-methylenebisacrylamide (MBAA, 99.9% Aladdin) were added to the above solution and stirred at room temperature until they were completely dissolved to obtain a mixed solution.

[0027] 3) The mixed solution was poured into a glass mold and polymerized at 60 °C for 1 h to obtain a zirconium phosphate nanosheet-enhanced hydrogel electrolyte. The water content of the obtained gel electrolyte was 67%.

[0028] Example 3 A zirconium phosphate nanosheet-enhanced hydrogel electrolyte is prepared by the following method: 1) Add 4 g of α-zirconium hydrogen phosphate and 8 mL of ethanolamine to 100 mL of deionized water and stir at room temperature for 48 h; w = 1000) to remove unreacted ethanolamine. The pH of the suspension after dialysis was about 7. The suspension was centrifuged at 10000 rpm / min for 2 min. The upper layer after centrifugation was the zirconium phosphate nanosheet dispersion. The solid content of zirconium phosphate in the dispersion was determined by calculating the mass ratio of the water solvent in the dispersion before and after drying. The solid content of the zirconium phosphate nanosheet was 2wt%, and the thickness of the prepared zirconium phosphate nanosheet was 2-4 nm.

[0029] 2) 4.26 g acrylamide monomer was dissolved in 10 mL 2 wt % zirconium phosphate nanosheet dispersion and then magnetically stirred at room temperature for 1 h; then 7.47 g ZnSO4·7H2O, 0.22 g MnSO4·H2O, 0.02 g initiator ammonium persulfate (APS, 99.9% Aladdin) and 0.002 g cross-linker N, N'-methylenebisacrylamide (MBAA, 99.9% Aladdin) were added to the above solution and stirred at room temperature until they were completely dissolved to obtain a mixed solution.

[0030] 3) The mixed solution was poured into a glass mold and polymerized at 60 °C for 5 h to obtain a zirconium phosphate nanosheet-enhanced hydrogel electrolyte. The water content of the obtained gel electrolyte was 60%.

[0031] Example 4 A zirconium phosphate nanosheet-enhanced hydrogel electrolyte is prepared by the following method: 1) Add 3 g of α-zirconium hydrogen phosphate and 5 mL of ethanolamine to 100 mL of deionized water and stir at room temperature for 48 h; w = 1000) to remove unreacted ethanolamine. The pH of the suspension after dialysis was about 7. The suspension was centrifuged at 10000 rpm / min for 2 min. The upper layer after centrifugation was the zirconium phosphate nanosheet dispersion. The solid content of the zirconium phosphate nanosheet in the dispersion was determined by calculating the mass ratio of the water solvent in the dispersion before and after drying. The solid content of the zirconium phosphate nanosheet was 1.5wt%, and the thickness of the prepared zirconium phosphate nanosheet was 2-4 nm.

[0032] 2) 3 g of acrylic acid monomer was dissolved in 10 mL of 1.5 wt % zirconium phosphate nanosheet dispersion and then magnetically stirred at room temperature for 1 h. Subsequently, 5.75 g of ZnSO4·7H2O, 0.17 g of MnSO4·H2O, 0.015 g of initiator ammonium persulfate (APS, 99.9% Aladdin) and 0.0015 g of cross-linker N, N'-methylenebisacrylamide (MBAA, 99.9% Aladdin) were added to the above solution and stirred at room temperature until they were completely dissolved to obtain a mixed solution.

[0033] 3) The mixed solution was poured into a glass mold and polymerized at 60 °C for 4 h to obtain a zirconium phosphate nanosheet-enhanced hydrogel electrolyte. The water content of the obtained gel electrolyte was 63%.

[0034] Example 5 A zirconium phosphate nanosheet-enhanced hydrogel electrolyte is prepared by the following method: 1) Add 2 g of α-zirconium hydrogen phosphate and 4 mL of ethanolamine to 100 mL of deionized water and stir at room temperature for 48 h. w = 1000) to remove unreacted ethanolamine. The pH of the suspension after dialysis was about 7. The suspension was centrifuged at 10000 rpm / min for 2 min. The upper layer after centrifugation was the zirconium phosphate nanosheet dispersion. The solid content of the zirconium phosphate nanosheet in the dispersion was determined by calculating the mass ratio of the water solvent in the dispersion before and after drying. The solid content of the zirconium phosphate nanosheet was 1wt%, and the thickness of the prepared zirconium phosphate nanosheet was 2-4 nm.

[0035] 2) 4 g of acrylamide monomer was dissolved in 10 mL of 1 wt % zirconium phosphate nanosheet dispersion and then magnetically stirred at room temperature for 1 h. Subsequently, 7.26 g of zinc trifluoromethanesulfonate, 0.02 g of initiator ammonium persulfate (APS, 99.9% Aladdin) and 0.002 g of cross-linker N, N'-methylenebisacrylamide (MBAA, 99.9% Aladdin) were added to the above solution and stirred at room temperature until they were completely dissolved to obtain a mixed solution.

[0036] 3) The mixed solution was poured into a glass mold and polymerized at 60 °C for 3 h to obtain a zirconium phosphate nanosheet-enhanced hydrogel electrolyte. The water content of the obtained gel electrolyte was 47%.

[0037] Performance Testing Test Example 1 The tensile strength and puncture strength of the zirconium phosphate nanosheet-enhanced hydrogel electrolyte obtained in Example 1 were tested and compared with those of the conventional polyacrylamide hydrogel electrolyte. Figure 1 and Figure 2 .from Figure 1 and Figure 2 The results show that compared with a single polymer gel electrolyte, the addition of zirconium phosphate nanosheets significantly improves the tensile strength and puncture strength of the gel electrolyte. This is because the zirconium phosphate two-dimensional nanosheets have a higher specific surface area, which can increase the interaction area and force with organic molecules and prevent inorganic materials from agglomerating. At the same time, the zirconium phosphate two-dimensional nano surface also contains abundant hydrophilic groups, which can form hydrogen bonds and electrostatic effects with polymers rich in hydrophilic groups, thereby improving the mechanical strength of the gel electrolyte.

[0038] Test Example 2 The performance of the zirconium phosphate nanosheet-enhanced hydrogel electrolyte prepared in Example 1 above was tested, and the specific testing method was as follows: 1) Positive electrode preparation: 90 wt% lithium manganese oxide, 5 wt% acetylene black, 2.5 wt% carboxymethyl cellulose and 2.5 wt% styrene butadiene rubber were added to a ball mill and milled at 300 rpm / min for 2 h. Deionized water was then added to adjust the solid content to 50%. The mixture was milled at 300 rpm / min for 4 h to obtain the positive electrode slurry. The positive electrode was scraped onto carbon paper using a scraper and heated at 60 °C. o C in a vacuum oven for 8 h, and then use a roller press to roll the electrode sheet to a compaction of 3.0 to obtain a positive electrode sheet. The mass surface loading of lithium manganese oxide in the positive electrode sheet is about 15 mg / cm 2 .

[0039] 2) Negative electrode preparation: Use 30 μm zinc foil as the electrode.

[0040] 3) The positive and negative electrodes were separated by the zirconium phosphate nanosheet-enhanced hydrogel electrolyte (ZrP-PAM), the liquid electrolyte-wetted separator (LE, 2mol / LZnSO4+1mol / Li2SO4) and the polyacrylamide hydrogel electrolyte (PAM) obtained in Example 1, respectively, and assembled in the order of positive electrode-electrolyte-negative electrode, and packaged with aluminum-plastic film to obtain different zinc ion batteries and perform performance tests respectively. The specific test results are shown in Figure 3-5 shown.

[0041] from Figure 3 It can be seen that the zinc ion battery prepared with zirconium phosphate nanosheets reinforced polyacrylamide hydrogel electrolyte has significantly higher zinc ion migration number and zinc ion conductivity than the other two electrolyte components. This is because the surface of zirconium phosphate nanosheets is zinc-philic, and the hydrophilic functional groups on the polymer surface can fix water molecules. Under the synergistic effect of the two, the zinc ion solvation structure can be changed, thereby promoting zinc ion transport.

[0042] like Figure 4 As shown in the figure, the prepared zirconium phosphate nanosheets reinforced composite hydrogel electrolyte improves the interface stability and long cycle performance. Compared with the traditional aqueous electrolyte and the single polymer gel electrolyte, the addition of zirconium phosphate nanosheets can inhibit the growth of zinc dendrites and promote the uniform deposition of zinc ions. Figure 5 As shown, compared with traditional aqueous electrolytes and single polymer gel electrolytes, high-performance zinc-ion batteries constructed with zirconium phosphate nanosheets enhanced hydrogel electrolytes exhibit longer cycle life at both room and high temperatures.

[0043] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

Claims

1. A method for preparing a zirconium phosphate nanosheet reinforced composite hydrogel electrolyte, characterized in that: It includes the following steps: (1) α-zirconium hydrogen phosphate, ethanolamine and deionized water are mixed to obtain a mixed solution, which is reacted at room temperature for 24-48 hours, and then unreacted ethanolamine is removed by dialyzing with a dialysis bag, and then the suspension is centrifuged at a certain speed, and the upper layer of the suspension after centrifugation is the zirconium phosphate nanosheet dispersion; (2) mixing the zirconium phosphate nanosheet dispersion, polymer monomer, initiator, cross-linking agent and metal salt in proportion at room temperature to obtain a gel electrolyte precursor solution; (3) Pour the above-mentioned gel electrolyte precursor solution into a glass mold and react at 60°C for 1-5 hours. After the reaction is completed, a zirconium phosphate nanosheet-reinforced composite hydrogel electrolyte is obtained.

2. The method for preparing the zirconium phosphate nanosheet reinforced composite hydrogel electrolyte according to claim 1, characterized in that: In the step (1), the mass fraction of α-zirconium hydrogen phosphate in the mixed solution is 1-4%, and the mass fraction of ethanolamine is 2-8%.

3. The method for preparing the zirconium phosphate nanosheet reinforced composite hydrogel electrolyte according to claim 1, characterized in that: The solid content of the zirconium phosphate nanosheet dispersion in step (1) is 0.5-2 wt %.

4. The method for preparing the zirconium phosphate nanosheet reinforced composite hydrogel electrolyte according to claim 1, characterized in that: The centrifugal separation speed in step (1) is 10000 rpm / min and the time is 2 min.

5. The method for preparing the zirconium phosphate nanosheet reinforced composite hydrogel electrolyte according to claim 1, characterized in that: The polymer monomer concentration in the gel electrolyte precursor solution is 2-6 mol / L, the initiator concentration is 3-9 mmol / L, the crosslinker concentration is 0.5-1.4 mmol / L, and the metal salt concentration is 2-3 mol / L.

6. The method for preparing the zirconium phosphate nanosheet reinforced composite hydrogel electrolyte according to claim 1 or 5, characterized in that: The polymer monomer is acrylamide or acrylic acid, the initiator is ammonium persulfate or potassium persulfate, and the crosslinking agent is N,N'-methylenebisacrylamide.

7. The method for preparing the zirconium phosphate nanosheet reinforced composite hydrogel electrolyte according to claim 1 or 5, characterized in that: The metal salt is a zinc salt, a mixed salt of a zinc salt and a manganese salt in a molar ratio of 20:1, or a mixed salt of a zinc salt and a lithium salt in a molar ratio of 2:1 or 1:

1.

8. The method for preparing the zirconium phosphate nanosheet reinforced composite hydrogel electrolyte according to claim 7, characterized in that: The zinc salt is one or more of zinc sulfate, zinc nitrate, zinc perchlorate, zinc acetate, zinc chloride, zinc trifluoromethanesulfonate, and zinc bis(trifluoromethylsulfonyl)imide; the lithium salt is one or more of lithium sulfate, lithium nitrate, lithium chloride, lithium perchlorate, lithium acetate, lithium trifluoromethanesulfonate, and lithium bis(trifluoromethanesulfonyl)imide; the manganese salt is one or more of manganese sulfate, manganese nitrate, manganese chloride, manganese perchlorate, and manganese acetate.

9. A zirconium phosphate nanosheet reinforced composite hydrogel electrolyte, characterized in that: The method according to claim 8 is used to prepare the product.

10. Use of the zirconium phosphate nanosheet reinforced composite hydrogel electrolyte according to claim 9 in an aqueous zinc ion battery.

Citation Information

Patent Citations

  • Zinc-based aqueous electrolyte with dynamic protection and application

    CN118040093A

  • Inorganic-organic gel electrolyte, preparation method thereof and application of inorganic-organic gel electrolyte in aqueous zinc-iodine battery

    CN118852500A

  • Proton conductive compound electrolyte membrane, membrane-electrode assembly and fuel cell using same, and method of manufacturing proton conductive compound electrolyte membrane

    JP2010244932A

  • Polyanionic zinc salt hydrogel electrolyte and zinc battery system

    WO2022057160A1